2010
DOI: 10.1055/s-0030-1249084
|View full text |Cite
|
Sign up to set email alerts
|

Alendronate Induces Mineralization in Mouse Osteoblastic MC3T3-E1 Cells: Regulation of Mineralization-Related Genes

Abstract: Alendronate, an aminobisphosphonate, is an effective reagent to reduce fracture risk in osteoporotic patients. Although several studies suggest that bisphosphonates affect osteoblast differentiation, how they affect the genes relating to the mineralization step remains unknown. The present study was performed to clarify the effects of alendronate on mineralization and its related genes in mouse osteoblastic MC3T3-E1 cells. Alendronate at 10 (-8) and 10 (-7) M induced mineralization in MC3T3-E1 cells. As for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Proliferation of MG63 cells was decreased when the cells were cultured on calcium phosphate [30][31][32]. We obtained the similar result to these reports when we cultured MG63 cells on CP.…”
Section: Discussionsupporting
confidence: 88%
“…Proliferation of MG63 cells was decreased when the cells were cultured on calcium phosphate [30][31][32]. We obtained the similar result to these reports when we cultured MG63 cells on CP.…”
Section: Discussionsupporting
confidence: 88%
“…Some researchers reported that alendronate enhanced the osteogenic differentiation of osteoblasts and bone marrow mesenchymal stem cells. 43,44) Moon et al 45) demonstrated that alendronate-immobilized titanium implant surface showed enhancement of osteoblast function as well as h and then decline gradually. McKenzie et al 48) also investigated the elution of zolendronic acid from a porous apatite-coated tantalum implant using a radio-labeling technique and claimed that the elution of zoledronic acids mainly localized in peri-implant bone, and peri-implant bone formation was strongly confined to the immediate space around the implant border.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel with our results, Runx2 expression was lower in alendronatetreated Rhesus monkeys with OVX, as compared with cathepsin K inhibitor-treated ones. 41 Since there is histological evidence of new bone formation in melatonin-or alendronate-treated OVX groups, it appears that bone mineralization observed in our study is not solely associated with the expression of the Runx2 gene, but other genes involved in osteoblast differentiation or osteoclast/bone resorption 42 could have more dominant roles in the in vivo regulatory mechanisms of alendronate or melatonin on osteoporotic bone tissue.…”
Section: Figurementioning
confidence: 66%